STRENGTHENING INDONESIA’S GREEN INVESTMENT LAW: Legal Reconceptualisation toward Net-Zero Emissions under Green Constitution and Maslahah - Supriyadi, Aditya Prastian; Lutfi, Mustafa; Bahagiati, Kurniasih (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
Indonesia’s green investment legal framework continues to exhibit substantive and institutional deficiencies, directly impeding the achievement of Net Zero Emissions targets and the broader national sustainable development agenda. This study employs a normative legal research method, utilising conceptual and statutory approaches, reinforced by doctrinal analysis of Green Constitution principles, the Islamic legal doctrine of maslahah, and Indonesia’s green investment and environmental governance policies. The findings reveal that the green investment legal framework has not ensured legal certainty, effective enforcement, or measurable environmental benefits due to regulatory fragmentation, weak integration of Environmental, Social, and Governance principles, and the absence of operationalisation of maslahah as a foundation for public policy; consequently, a reformulation of the legal paradigm is required, emphasising transparency, institutional accountability, and risk-based regulatory approaches to strengthen environmental protection and climate justice, support the achievement of Sustainable Development Goal 13, enhance cross-sectoral green investment instruments, improve inter-institutional coordination, and align national policies with commitments under the Paris Agreement and the global sustainable development agenda in a consistent, measurable, adaptive, and socio-ecologically just manner. This research helps formulate a more climate-responsive and public welfare-oriented green investment legal model as a foundational framework for sustainable environmental policy-making in Indonesia, with implications for global environmental sustainability. Kerangka hukum investasi hijau di Indonesia masih menghadapi berbagai kelemahan substantif dan institusional yang berimplikasi langsung pada terhambatnya pencapaian target Net Zero Emissions dan agenda pembangunan berkelanjutan nasional. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan konseptual dan peraturan perundang-undangan, yang diperkaya melalui analisis doktrinal terhadap prinsip Green Constitution, doktrin maslahah dalam hukum Islam, serta kerangka kebijakan investasi hijau dan tata kelola lingkungan di Indonesia. Hasil penelitian menunjukkan bahwa kerangka hukum investasi hijau yang berlaku belum memberikan kepastian hukum, efektivitas penegakan, maupun manfaat lingkungan yang terukur akibat fragmentasi regulasi, lemahnya integrasi prinsip Environmental, Social, and Governance, serta belum teroperasionalisasinya nilai maslahah sebagai dasar kebijakan publik, sehingga diperlukan reformulasi paradigma hukum yang menekankan transparansi, akuntabilitas kelembagaan, dan pendekatan regulasi berbasis risiko dalam rangka memperkuat perlindungan lingkungan dan keadilan iklim, guna mendukung pencapaian Sustainable Development Goal 13 melalui penguatan instrumen investasi hijau lintas sektor, peningkatan koordinasi antar lembaga, penyelarasan kebijakan nasional dengan komitmen Paris Agreement dan agenda pembangunan berkelanjutan global secara konsisten, terukur, adaptif, dan berkeadilan sosial ekologis nasional berkelanjutan Indonesia. Kontribusi penelitian adalah perumusan model konseptual hukum investasi hijau yang proporsional, responsif terhadap perubahan iklim, berorientasi pada kesejahteraan umum sebagai fondasi kebijakan lingkungan berkelanjutan di Indonesia dan berimplikasi pada keberlanjutan lingkungan global.